SENYAWA KIMIA AKTIF PADA DAUN NIPAH (Nyfa fruticans Wurmb) - Laely Wijayanti; Rosidah Radam; Siti Hamidah (Universitas Lambung Mangkurat, 2022)
Nipah plants are plants that live in brackish water swamp ecosystems and river mouths. Nipah is often used for various household needs. Nipah contains active compounds that can become medicinal plants. This research has purpose to analyze active chemical compounds in three age of nipah leaves in young, medium, and old periode.This research was conducted at the Lambung Mangkurat Banjarbaru Forest Product Technology Laboratory. The study time was conducted for 4 including the stages of material preparation and equipment, laboratory analysis, data processing, preparation and writing of research results. The study was conducted by conducting phytochemical testing by identifying triterpenoids, alkaloids, steroids, and flavonoids. Simplisia is carried out 3 times repetition at each age of the nipah leaves. Young, medium, and old leaves from the test results obtained active chemical compounds, namely alkaloid compounds, triterpenoids, flavonoids, and tannins. Medium and old leaves contain steroids, while young leaves do not exist. Young leaves contain triterpenoids, while medium leaves and old leaves do not contain triterpenoids.Tanaman Nipah merupakan tanaman yang hidup dalam ekosistem rawa air payau dan muara sungai. Nipah sering dimanfaatkan untuk berbagai keperluan rumah tangga. Nipah memiliki kandungan senyawa aktif yang dapat menjadi tumbuhan berkhasiat obat. Penelitian ini bertujuan untuk menganalisis kandungan senyawa kimia aktif pada daun nipah berumur muda, sedang dan tua. Penelitian ini dilaksanakan di Laboratorium Teknologi Hasil Hutan Universitas Lambung Mangkurat Banjarbaru. Waktu penelitian dilaksanakan selama 4 meliputi tahapan persiapan bahan dan peralatan, analisis laboratorium, pengolahan data, penyusunan dan penulisan hasil penelitian. Penelitian dilakukan dengan melakukan pengujian fitokimia dengan mengidentifikasi Triterpenoid, Alkaloid, Steroid, dan Flavonoid. Simplisia dilakukan 3 kali pengulangan pada setiap umur dari daun nipah. Daun muda, sedang, dan tua dari hasil uji didapat senyawa kimia aktif yaitu senyawa Alkaloid, Triterpenoid, Flavonoid, dan Tannin. Daun sedang dan tua mengandung steroid, sedangkan daun muda tidak ada. Daun muda mengandung Triterpenoid, sedangkan daun yang sedang dan daun yang tua tidak mengandung Triterpenoid.